Intercellular transfer of transferrin receptor by a contact‐, Rab8‐dependent mechanism involving tunneling nanotubes. Issue 11 (28th July 2015) - Burtey, Anne; Wagner, Marek; Hodneland, Erlend; Skaftnesmo, Kai Ove; Schoelermann, Julia; Mondragon, Ivan Rios; Espedal, Heidi; Golebiewska, Anna; Niclou, Simone P.; Bjerkvig, Rolf; Kögel, Tanja; Gerdes, Hans‐Hermann
ABSTRACT: Intercellular communication between cancer cells, especially between cancer and stromal cells, plays an important role in disease progression. We examined the intercellular transfer of organelles and proteins in vitro and in vivo and the role of tunneling nanotubes (TNTs) in this process. TNTs are membrane bridges that facilitate intercellular transfer of organelles of unclear origin. Using 3‐dimensional quantitative and qualitative confocal microscopy, we showed that TNTs contain green fluorescent protein (GFP)‐early endosome antigen (EEA) 1, GFP Rab5, GFP Rab11, GFP Rab8, transferrin (Tf), and Tf receptor (Tf‐R) fused to mCherry (Tf‐RmCherry). Tf‐RmCherry was transferred between cancer cells by a contact‐dependent but secretion‐independent mechanism. Live cell imaging showed TNT formation preceding the transfer of Tf‐RmCherry and involving the function of the small guanosine triphosphatase (GTPase) Rab8, which colocalized with Tf‐RmCherry in the TNTs and was cotransferred to acceptor cells. Tf‐RmCherry was transferred from cancer cells to fibroblasts, a noteworthy finding that suggests that this process occurs between tumor and stromal cells in vivo. We strengthened this hypothesis in a xenograft model of breast cancer using enhanced (e)GFP‐expressing mice. Tf‐RmCherry transferred from tumor to stromal cells and this process correlated with an increased opposite transfer of eGFP from stromal to tumor cells, together pointing toward complex intercellular communication at the tumor site.—Burtey, A., Wagner, M., Hodneland, E., Skaftnesmo, K. O., Schoelermann, J., Mondragon, I. R., Espedal, H., Golebiewska, A., Niclou, S. P., Bjerkvig, R., Kögel, T., Gerdes, H.‐H. Intercellular transfer of transferrin receptor by a contact‐, Rab8‐dependent mechanism involving tunneling nanotubes. FASEB J. 29, 4695‐4712 (2015). www.fasebj.org